Early clinical trial unit tumor board: a real-world experience in a national cancer network - Weiss, L.; Dorman, K.; Boukovala, M.; Schwinghammer, F.; Jordan, P.; Fey, T.; Hasselmann, K.; Subklewe, M.; Bücklein, V.; Bargou, R.; Goebeler, M.; Sayehli, C.; et al. (Journal of Cancer Research and Clinical Oncology, 2023)
Purpose: Early clinical trials are the first step into clinical therapies for new drugs. Within the six Bavarian university-based hospitals (Augsburg, Erlangen, Regensburg, Munich (LMU and TU), Würzburg) we have enrolled a virtual network platform for patient discussion. Methods: The virtual Early Clinical Trial Unit Tumor Board (ECTU Tumor Board) is a secured web-based meeting to evaluate early clinical trial options for patients, where representatives from local ECTUs participate. We retrospectively analyzed patient cases discussed between November 2021 and November 2022. Results: From November 2021 to November 2022, a total of 43 patients were discussed in the ECTU Tumor Board. Median age at diagnosis was 44.6 years (range 10–76 years). The median number of previous lines of therapies was 3.7 (range 1–9 therapies) including systemic treatment, surgery, and radiation therapy. A total of 27 different tumor entities were presented and 83.7% (36/43) patients received at least one trial recommendation. In total, 21 different active or shortly recruiting clinical trials were recommended: ten antibody trials, four BiTE (bispecific T cell engager) trials, six CAR (chimeric antigen receptor) T-cell trials, and one chemotherapy trial. Only six trials (28.6%) were recommended on the basis of the previously performed comprehensive genetic profiling (CGP). Conclusion: The ECTU Tumor Board is a feasible and successful network, highlighting the force of virtual patient discussions for improving patient care as well as trial recruitment in advanced diseases. It can provide further treatment options after local MTB presentation, aiming to close the gap to access clinical trials.
CRIS-Team Scopus Importer:2023-08-04
Keywords: Clinical trials; Early clinical trial; ECTU; Interdisciplinary; Precision oncology; Tumor board